Degradable biocomposite membrane based on protein fiber reinforcement and preparation method and application thereof

By adding specific treatment protein fibers as reinforcement to the degradable biocomposite membrane, the problems of insufficient mechanical properties and water vapor permeability of the existing composite membrane are solved, and stronger tensile strength and oxidation resistance are achieved, achieving the effect of food preservation.

CN116284897BActive Publication Date: 2025-03-14QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310044667.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-30
Publication Date
2025-03-14
Estimated Expiration
2043-01-30

AI Technical Summary

Technical Problem

The existing degradable biocomposite membranes have shortcomings in mechanical properties and water vapor permeability, which are difficult to meet the needs of food preservation.

Method used

The protein fiber solution is prepared by adding protein fibers as a reinforcement to the solution of biodegradable polymer material, and the protein fiber solution is prepared by acid, heat and alkali treatment, and a degradable biocomposite membrane based on protein fiber reinforcement is prepared in combination with glycerin and water.

Benefits of technology

It significantly improves the tensile strength and oxidation resistance of the composite film, reduces the permeability of water vapor, and effectively avoids the large loss of food moisture and achieves a better preservation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284897B_ABST
    Figure CN116284897B_ABST
Patent Text Reader

Abstract

The present invention discloses a degradable biocomposite film based on protein fiber reinforcement, a preparation method and an application. The degradable biocomposite film based on protein fiber reinforcement claimed in the present invention is prepared from a biodegradable polymer material solution, a protein fiber solution, glycerol and water, wherein the protein fiber solution refers to a protein fiber solution obtained by sequentially subjecting the protein to acid treatment, heat treatment and alkali treatment, and the pH value of the protein fiber solution is 2.0-7.0. A degradable biocomposite film provided by the present invention can effectively avoid a large amount of water loss in food to achieve a better preservation effect; the tensile strength result is not less than 9.0MPa, and the practicality is enhanced; the DPPH free radical scavenging rate is not less than 60%, and the ABTS free radical scavenging rate is not less than 70%. Therefore, the degradable biocomposite film prepared by the present application has a good application effect in terms of anti-oxidation of food.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food packaging, and in particular relates to a degradable biocomposite film based on protein fiber reinforcement, a preparation method and an application thereof. Background Art

[0002] Since petroleum-based plastic films are non-biodegradable and can cause serious environmental pollution, renewable polymer films have gradually become the research and development focus of scientific researchers in recent years. At present, biodegradable film-forming polymer materials such as starch, polysaccharides, proteins, chitosan, cellulose and chitin are widely used in research due to their environmental and economic advantages, and will occupy a large market in the future.

[0003] Compared with petroleum-based plastic films, existing biodegradable biocomposite films still have some shortcomings, such as low mechanical properties and poor water vapor permeability. Therefore, it is necessary to add a reinforcing agent to improve them. At present, there is no report on the application of protein fiber as a reinforcing agent in biodegradable biocomposite films. Summary of the invention

[0004] The purpose of the present invention is to solve the problems raised in the above background technology, and to provide a degradable biocomposite membrane based on protein fiber reinforcement, a preparation method and an application thereof.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A degradable biocomposite membrane reinforced with protein fibers, which is prepared from a biodegradable polymer material solution, a protein fiber solution, glycerol and water. The protein fiber solution is obtained by sequentially treating protein with acid, heat and alkali, and the pH value of the protein fiber solution is 2.0-7.0.

[0007] Preferably, the mass fraction of protein fibers in the protein fiber solution is greater than 2.0%.

[0008] Preferably, the protein fiber is whey protein isolate fiber or soy protein fiber.

[0009] Preferably, the protein fiber solution is obtained by the following preparation method, which comprises the following steps: subjecting the protein solution to acid treatment to obtain a treatment solution with a pH of 1.0-3.0, at which time, the protein is hydrolyzed, the peptide bonds are broken, and polypeptides are formed; then heat treatment is performed, i.e., heating in a water bath at 75-90°C for 8-10 hours, continuously stirring magnetically during the heating process, and then immediately immersing the treatment solution in an ice-water mixture and allowing it to stand to stop the reaction. After the above-mentioned heat treatment, the protein unfolds, the rate of peptide bond breaking is accelerated, the polypeptides undergo β-folding stacking, and linear fibers are formed through non-covalent interactions; then alkali treatment is performed to adjust the pH value of the treatment solution to 2.0-7.0 to obtain a protein fiber solution. Alkali treatment can change the morphology of the fibers, and the fiber length becomes shorter and aggregates within this pH range.

[0010] Preferably, the protein solution is treated with an inorganic acid to obtain a treatment solution with a pH of 1.0-3.0.

[0011] Preferably, the alkaline treatment is performed using an inorganic base to adjust the pH value of the treatment solution to 2.0-7.0.

[0012] Preferably, the inorganic acid is phosphoric acid or hydrochloric acid.

[0013] Preferably, the inorganic base is sodium hydroxide or potassium hydroxide.

[0014] Preferably, the protein solution is treated with an inorganic acid to obtain a treatment solution with a pH of 2.0; and during the heat treatment, the water bath heating time is 10 hours.

[0015] Preferably, the biodegradable polymer material is one or more of polysaccharides and proteins.

[0016] Preferably, the polysaccharide comprises common starch, modified starch, chitosan, konjac glucomannan and pectin.

[0017] Preferably, the protein comprises gelatin, soy protein and soy protein isolate.

[0018] A method for preparing a degradable biocomposite membrane based on protein fiber reinforcement comprises the following steps:

[0019] Step S1, mixing the biodegradable polymer material solution, glycerol and water, and stirring evenly at 45° C.-90° C. to obtain a standby solution;

[0020] Step S2, preparing a protein fiber solution;

[0021] Step S3, cooling the standby solution to 40° C., then adding the protein fiber solution to the standby solution, stirring evenly, to obtain a film-forming solution;

[0022] Step S4: Dry the film-forming solution prepared in step S3 in an oven, and place it in a dryer at room temperature and constant relative humidity for two days.

[0023] Preferably, in step S1, when the degradable polymer material solution is a polysaccharide solution or a protein solution, the mass fraction of the degradable polymer material is 3%-10%; when the degradable polymer material solution contains polysaccharides and proteins, the mass fraction of the polysaccharide is 1%-9%, and the mass fraction of the protein is 9%-1%.

[0024] Preferably, in step S1, the mass ratio of glycerol to the degradable polymer material in the degradable polymer material solution is (0.2-0.5):1.

[0025] Preferably, in step S1, when the biodegradable polymer material solution is a polysaccharide solution, the biodegradable polymer material solution, glycerol and water are mixed and stirred evenly at 90°C; when the biodegradable polymer material solution is a protein solution, the biodegradable polymer material solution, glycerol and water are mixed and stirred evenly at 45°C.

[0026] Preferably, in step S3, the mass of the protein fibers in the membrane-forming solution accounts for ≤2% of the total mass of the membrane-forming solution.

[0027] The invention discloses an application of a degradable biocomposite film reinforced with protein fibers in food preservation.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. In this application, non-toxic, nutritious, easy to digest, sustainable and inexpensive food proteins are used to modify biodegradable polymer materials. In this application, glycerol plays the role of a plasticizer, and protein fibers play the role of a reinforcing agent. In this application, protein fibers are a kind of nanomaterials. Under low ionic strength and pH values ​​far from their isoelectric points, they will self-assemble to form linear fibers of micrometer length and nanometer diameter after long-term heating. Moreover, the physical rigidity of the degradable biocomposite film prepared in this application is also strong. In this application, the acid-treated protein is unfolded, and the cysteine ​​residues with redox activity inside are exposed on the surface, so that the protein fiber has high antioxidant properties, which is beneficial to improve the free radical scavenging rate as an antioxidant, and helps to inhibit the color change during the preservation of fruits and vegetables. Moreover, there are extensive functional groups on the surface of the protein fiber in this application, which promotes the interaction with the biodegradable polymer material, thereby closely combining to form a dense network structure, increasing the migration path of water molecules, reducing the water vapor permeability of the degradable biocomposite film, and helping to reduce the loss of water in the preservation process of fruits and vegetables for preservation.

[0030] The preparation method of the protein fiber-reinforced degradable biocomposite membrane claimed in the present application can significantly improve the tensile strength and oxidation resistance of the composite membrane and reduce the water vapor permeability of the composite membrane through simple operations. In addition, the raw materials described in the present invention are widely available, low in price, and have high production and application value; and the present application can further expand the application of protein fibers in the fields of food and chemical industries.

[0031] In addition, experimental tests show that the water vapor permeability of the biodegradable biocomposite membrane provided by the present invention is 2.374×10 -12 -2.441×10 -12 (g·cm / cm 2 ·s·Pa), which is significantly lower than the water vapor permeability of the biodegradable biocomposite membrane without protein fiber addition (2.677×10 -12 (g·cm / cm 2 ·s·Pa), which can effectively avoid a large amount of water loss in food to achieve a better preservation effect; the tensile strength result is not less than 9.0MPa, which is significantly higher than the tensile strength of the degradable biocomposite film without added protein fiber, and the practicality is enhanced; the DPPH free radical scavenging rate is not less than 60%, and the ABTS free radical scavenging rate is not less than 70%. Therefore, the degradable biocomposite film prepared in the present application has a good application effect in the anti-oxidation of food. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1A is a transmission electron micrograph of the protein fiber morphology in the protein fiber solution in Example 1, Figure 1A The scale bar in the middle is 1 μm;

[0033] Figure 1B is a transmission electron micrograph of the protein fiber morphology in the protein fiber solution in Example 7, Figure 1B The scale bar in the middle is 1 μm;

[0034] Figure 1C For Figure 1A Statistical chart for fiber length and fiber quantity;

[0035] Figure 1D For Figure 1B Statistical chart for fiber length and fiber quantity;

[0036] Figure 2 FTIR spectra of the degradable biocomposite films obtained in Examples 1-3 and Comparative Example 1.

[0037] Figure 3 The XRD patterns of the degradable biocomposite films obtained in Examples 1-3 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] A method for preparing a degradable biocomposite membrane based on protein fiber reinforcement comprises the following steps:

[0041] Step S1, mixing 50 g of a 10% starch solution, 1.5 g of glycerol and 45 g of water, stirring at 90° C. for 30 minutes, stirring evenly, to obtain a standby solution;

[0042] Step S2, preparing a protein fiber solution: weighing 4 g of whey protein isolate powder and dissolving it in 100 g of sterile water, fully dissolving it, and preparing a whey protein isolate solution with a mass fraction of 4%; then, adjusting the pH of the whey protein isolate solution to 2.0 using phosphoric acid to obtain a treated solution; then, heating the treated solution in a water bath at 80° C. for 10 hours, continuously stirring the solution with magnetic force during the heating process, and then immediately immersing the treated solution in an ice-water mixture and allowing it to stand for 20 minutes to stop the reaction; then, adjusting the pH value of the treated solution to 2.0 using a sodium hydroxide solution to obtain a whey protein isolate fiber solution with a mass fraction of 4% and a pH of 2.0;

[0043] Step S3, cooling the standby solution to 40°C, adding 5 g of the whey protein isolate fiber solution with a mass fraction of 4% and a pH of 2.0 obtained in step S2 to the standby solution in step S1, and stirring for 10 minutes until uniform, to obtain a film-forming solution; the mass of the protein fiber in the film-forming solution accounts for 0.2% of the total mass of the film-forming solution;

[0044] Step S4, pour the film-forming solution prepared in step S3 into a flat plate, place it in an oven and dry it at 30°C for 14 hours, and then place it in a dryer at room temperature and constant relative humidity for two days to obtain a degradable biocomposite membrane reinforced with protein fibers.

[0045] Example 2-Example 4

[0046] Compared with Example 1, Examples 2 to 4 are the same as Example 1, except that the mass of water added in step S1 is 40g, 35g and 0g respectively, and the whey isolate protein fiber solution added in step S3 is 10g, 15g and 50g respectively, that is, the percentage of the mass of protein fiber in the film-forming solution to the total mass of the film-forming solution is 0.4%, 0.6% and 2.0% respectively.

[0047] Embodiment 5-7

[0048] The difference between Examples 5 to 7 and Example 1 is that in step S2 of Examples 5 to 7, the pH value of the treatment liquid is adjusted to 3.0, 6.0, and 7.0 using sodium hydroxide solution, respectively, to obtain whey protein isolate fiber solutions with a pH of 3.0, 6.0, and 7.0, respectively, and a mass fraction of 4%, and the rest are the same as Example 1.

[0049] Example 8-Example 14

[0050] The experimental conditions of Examples 8 to 14 are set corresponding to those of Examples 1 to 7, respectively, with the difference being that the starch in step S1 in Examples 8 to 14 is replaced by gelatin, the stirring temperature is replaced by 90°C to 45°C, and the remaining reaction conditions in Examples 8 to 14 are set corresponding to the experimental conditions of Examples 1 to 7, respectively.

[0051] Examples 15-21

[0052] The experimental conditions of Examples 15 to 21 are set corresponding to those of Examples 1 to 7, respectively, with the difference being that in Step S2 of Examples 15 to 21, the whey protein isolate powder is replaced with soy protein powder, that is, soy protein fiber solution is prepared in Step S2 of Examples 15 to 21; and the remaining reaction conditions of Examples 15 to 21 are set corresponding to the experimental conditions of Examples 1 to 7, respectively.

[0053] Examples 22-28

[0054] The experimental conditions of Examples 22 to 28 are set corresponding to those of Examples 1 to 7, except that: in step S2 of Examples 15 to 21, the whey protein isolate powder is replaced with soy protein powder, soy protein fiber solution is prepared in step S2 of Examples 15 to 21, the starch in step S1 of Examples 22 to 28 is replaced with gelatin, and the stirring temperature is replaced from 90°C to 45°C; the remaining reaction conditions in Examples 22 to 28 are set corresponding to the experimental conditions of Examples 1 to 7.

[0055] Comparative Example 1

[0056] Comparative Example 1 is compared with Example 1, except that the mass of water in step S1 is 50g, and no whey protein isolate fiber solution is added in step S3, the rest is the same as Example 1.

[0057] Comparative Example 2-Comparative Example 3

[0058] Comparative Examples 2 and 3 are the same as Example 1 except that the pH of the whey protein isolate fiber solution adjusted with sodium hydroxide solution in step S2 of Comparative Examples 2 and 3 is 9.0 and 10.0 respectively.

[0059] Comparative Example 4-Comparative Example 6

[0060] Comparative Examples 4 to 6 are respectively arranged relative to Comparative Examples 1 to 3. In Comparative Examples 4 to 6, except that the starch in step S1 is replaced with gelatin, the other experimental conditions in Comparative Examples 4 to 6 are the same as those in Comparative Examples 1-3.

[0061] Comparative Example 7-Comparative Example 9

[0062] Comparative Examples 7 to 9 are respectively set up relative to Comparative Examples 1-3. In Comparative Examples 7 to 9, except that the whey protein isolate powder in step S2 is replaced by soy protein powder, that is, the soy protein fiber solution is prepared in step S2, the other experimental conditions in Comparative Examples 7 to 9 are the same as those in Comparative Examples 1-3.

[0063] Comparative Example 10-Comparative Example 12

[0064] Comparative Examples 10 to 12 are respectively arranged relative to Comparative Examples 1-3. In Comparative Examples 10 to 12, except that the whey protein isolate powder in step S2 is replaced by soy protein powder, that is, the soy protein fiber solution is prepared in step S2, the starch in step S1 is replaced by gelatin, and the other experimental conditions in Comparative Examples 10 to 12 are the same as those in Comparative Examples 1-3.

[0065] Experimental testing

[0066] 1. Water vapor permeability test

[0067] Water vapor permeability (WVP) is measured using a water vapor transmission rate tester PERME TM W3 / 030 (Lab think Instrument Co., Ltd., Jinan, China) was used to measure the above Examples 1-6 and Comparative Examples 1-5. During the measurement process, the sample was first cut into pieces with an area of ​​33 cm using a special mold. 2 Then, keep it at 38℃ and 90%RH for 12 hours. Repeat the experiment three times and take the average value.

[0068] 2. Mechanical strength determination

[0069] The degradable biocomposite membranes based on protein fiber reinforcement were cut into 1×7 cm and the tensile strength was determined using an automatic tensile tester (Param Xlw, Jinan, China). The speed of the crosshead was set to 50 mm / min. Each test membrane was repeated at least 5 times. The value of tensile strength (TS, MPa) was obtained from the automatic tensile tester.

[0070] 3. Determination of antioxidant properties

[0071] 2 g of the protein fiber-reinforced degradable biocomposite membrane was immersed in 100 mL of distilled water, then shaken at 150 rpm and 25° C. for 1 hour, and centrifuged at 3000 g for 10 minutes to remove undissolved substances, to obtain the dissolved supernatant of the degradable biocomposite membrane for use.

[0072] 3.1DPPH free radical scavenging rate

[0073] 1.0 mL of the supernatant of the degradable biocomposite film solution was added to 4.0 mL of a mixed solvent of DPPH and ethanol, wherein the molar concentration of DPPH in the mixed solvent was 0.1 mM, and the ethanol used in the mixed solvent was 95% ethanol by mass. The solution was then mixed vigorously and placed in the dark at room temperature for 30 minutes. The absorbance of the mixture was measured at 517 nm using a Shimadzu UV-2500 spectrophotometer. The results were calculated as the inhibition percentage according to the following formula:

[0074]

[0075] A i is the absorbance of the supernatant containing the protein fiber composite membrane, is the absorbance of the membrane supernatant obtained in the comparative example without adding protein fiber, A c It is the absorbance of a blank consisting of 4.0 mL of a mixed solvent of DPPH and ethanol and 1.0 mL of distilled water.

[0076] 3.2 ABTS free radical scavenging rate

[0077] 0.1 mL of the supernatant of the degradable biocomposite film solution was mixed with 3.9 mL of ABTS reagent, and then the mixture was kept in the dark for 10 minutes, and the absorbance at 734 nm was measured.

[0078]

[0079] A i is the absorbance of the supernatant of the biodegradable composite membrane, and A0 is the absorbance of a blank consisting of 0.1 mL of distilled water and 3.9 mL of ABTS reagent.

[0080] The WVP, mechanical strength and antioxidant properties of the starch-degradable biocomposite membranes reinforced with whey protein isolate fibers prepared in Examples 1-7 and Comparative Examples 1-3 were statistically analyzed. The results are shown in Table 1.

[0081] Table 1

[0082]

[0083]

[0084] The WVP, mechanical strength and antioxidant properties of the whey protein isolate fiber-reinforced gelatin-degradable biocomposite membranes prepared in Examples 8-14 and Comparative Examples 4-6 were statistically analyzed. The results are shown in Table 2.

[0085] Table 2

[0086]

[0087]

[0088] The WVP, mechanical strength and antioxidant properties of the soybean protein fiber-reinforced starch-degradable biocomposite films prepared in Examples 15-21 and Comparative Examples 7-9 were statistically analyzed. The results are shown in Table 3.

[0089] Table 3

[0090]

[0091]

[0092] The WVP, mechanical strength and antioxidant properties of the soy protein fiber reinforced gelatin biodegradable composite films prepared in Examples 22-28 and Comparative Examples 10-12 were statistically analyzed. The results are shown in Table 4.

[0093] Table 4

[0094]

[0095]

[0096] From Table 1-4, we can know that:

[0097] 1. Optimization of protein fiber concentration:

[0098] When only the concentration of protein fiber was used as the variable factor, the water vapor permeability WVP values ​​of the films of Examples 1-4, 8-11, 15-18 and 22-25 were all within 2.441×10 -12 g cm / cm 2·s·Pa, the tensile strength TS value is above 9.0MPa, and the DPPH free radical scavenging rate and ABTS free radical scavenging rate are above 60% and 70%, respectively. No protein fiber was added to Comparative Examples 1, 4, 7 and 10. The WVP values ​​of the membranes of Examples 1-4, 8-11, 15-18 and 22-25 and the WVP values ​​of Comparative Examples 1, 4, 7 and 10 were compared. When no protein fiber was added to the degradable biocomposite membrane, the water vapor permeability WVP value of the membrane would increase. Moreover, it is clear from the data in Tables 1 to 4 that the water vapor permeability of the membranes of Comparative Examples 1, 4, 7 and 10 is much higher than that of the corresponding embodiments, among which the water vapor permeability of the membranes of Comparative Examples 1, 4, 7 and 10 can be up to 16.5% higher than that of the corresponding embodiments.

[0099] In addition, the tensile strength TS values ​​of Comparative Examples 1, 4, 7 and 10 are all around 7.0 MPa, which are significantly lower than those of the corresponding embodiments, and the lowest can be lower than 138%;

[0100] Moreover, the test results of Examples 1-4, 8-11, 15-18 and 22-25 also show that the DPPH free radical scavenging rate and the ABTS free radical scavenging rate will increase with the increase of protein fiber concentration. Because the presence of protein fiber can form a dense network structure in the degradable biocomposite membrane, on the one hand, the increase in the migration path of water molecules in the degradable biocomposite membrane is relatively small, thereby reducing the water vapor permeability WVP of the membrane; on the other hand, the dense network structure will also increase the rigidity of the degradable biocomposite membrane, thereby significantly increasing the tensile strength TS. However, it can be found that the water vapor permeability WVP shows a trend of first decreasing and then increasing with the concentration of protein fiber, and the tensile strength TS shows a trend of first increasing and then decreasing with the concentration of protein fiber. When the concentration of added protein fiber is higher than 2.0%, the protein fiber will be aggregated, resulting in a larger aggregation degree and range of pores in the degradable biocomposite membrane, which is conducive to increasing the water vapor permeability WVP and reducing the tensile strength TS. Taking into account the comprehensive reduction of the performance of the degradable biocomposite membrane, the addition of protein fiber is preferred for the degradable biocomposite membrane, and the protein fiber concentration ≤2.0% is the preferred concentration.

[0101] 2. Optimize the pH value of protein fiber.

[0102] Alkali treatment to adjust the pH value of protein fiber solution can significantly change the morphology of protein fibers, such as fiber length, e.g. Figures 1A to 1D As shown, the structure and performance of the degradable biocomposite membrane are affected. The above experiments show that when the pH of the protein fiber solution is 2.0-7.0 (Examples 5-7, 12-14, 19-21 and 26-28), the water vapor permeability WVP value of the degradable biocomposite membrane is 2.374×10 -12 g cm / cm2 ·s·Pa, the tensile strength TS value is above 9.0MPa, the DPPH free radical scavenging rate and the ABTS free radical scavenging rate are above 60% and 70%, respectively. When the pH is increased to 9 or 10 (Comparative Examples 2-3, 5-6, 8-9 and 11-12), the water vapor permeability WVP value increases. The water vapor permeability WVP value of Comparative Examples 2-3, 5-6, 8-9 and 11-12 can be increased by up to 11.1% compared with the water vapor permeability WVP value of the corresponding embodiment;

[0103] Moreover, the tensile strength TS values ​​of the degradable biocomposite films prepared in Comparative Examples 2-3, 5-6, 8-9 and 11-12 are also about 7.5 MPa, which is significantly lower than that of the corresponding embodiments. The tensile strength TS values ​​of Comparative Examples 2-3, 5-6, 8-9 and 11-12 can be reduced by as little as 68.1% compared with the tensile strength TS of the corresponding embodiments;

[0104] According to experimental test data, the DPPH free radical scavenging rate and ABTS free radical scavenging rate have better effects when the pH of the protein fiber solution is 2.0-3.0. This is mainly because when the pH rises to 9, 10 or above, the alkalinity is too strong, which will affect the linear morphology of the protein fiber, and the fiber length is too short to form a relatively complete network structure in the membrane, and it is impossible to increase the tensile strength TS of the degradable biocomposite membrane, so that the rigidity of the degradable biocomposite membrane cannot be increased, reducing the role of the protein fiber as a reinforcing agent and reducing the performance of the composite membrane.

[0105] In addition, it can be seen from Tables 1-4 that when the percentage of protein fiber mass in the film-forming solution to the total mass of the film-forming solution is ≤2.0% and the pH is 2.0-7.0, the water vapor permeability WVP value of the degradable biocomposite membrane is low, the tensile strength TS is large, the DPPH free radical scavenging rate and the ABTS free radical scavenging rate are both high, the antioxidant property is good, and the effect is optimal.

[0106] 3. Test of protein fiber morphology

[0107] The present application also measures the protein fiber morphology of Example 1 and Example 7. The pH of the whey protein isolate fiber solution obtained in Example 1 is 2.0, and the pH of the whey protein isolate fiber solution obtained in Example 7 is 7.0. The morphology is observed by a transmission electron microscope (JEM-1400F, Japan Electronics Corporation). In order to better observe the morphology of the whey protein isolate fiber, the present application specifically dilutes the whey protein isolate fiber solution prepared in Example 1 and Example 7 until the mass fraction of the whey protein isolate fiber in the whey protein isolate fiber solution is 0.04%, and then, 10 μL of the diluted whey protein isolate fiber solution is dripped onto a 300-mesh copper mesh, and after drying, the protein fiber is stained with 10 g / L phosphotungstic acid, and then the excess liquid is sucked away with filter paper, and the protein fiber morphology is observed microscopically after the copper mesh is completely dried. The observation results are as follows: Figure 1A and Figure 1B As shown, at the same time, this application also respectively 1A and Figure 1B The fiber length and fiber quantity were counted. Figure 1C and Figure 1D shown.

[0108] from Figure 1A It can be seen that the whey protein isolate fibers in the whey protein isolate fiber solution obtained in Example 1 show elongated fibrils, and Figure 1C It can be seen that the average contour length of the whey protein isolate fibers in the whey protein isolate fiber solution obtained in Example 1 is about 1418 nm, indicating that the whey protein isolate fibers have a micrometer length.

[0109] from Figure 1B It can be seen that the whey protein isolate fiber solution obtained in Example 7 has a shortened length of whey protein isolate fibers and produces a small amount of aggregates. Figure 1D It can be seen that the average length of the whey protein isolate fibers in the whey protein isolate fiber solution obtained in Example 7 is about 499 nm, and the length of the protein fibers becomes shorter. This is due to the strong aggregation and breakage of the protein fibers near the isoelectric point of the fibers. Therefore, the addition of linear protein fibers helps to form a degradable biocomposite membrane with a stable network structure.

[0110] 4. Testing of degradable biocomposite membranes

[0111] 4.1 Fourier transform infrared spectroscopy of degradable biocomposite membranes

[0112] The FTIR spectra of the degradable biocomposite membranes of Examples 1-3 and Comparative Example 1 were observed using a Fourier transform infrared spectrometer (PerkinElmer, Shelton, USA). The degradable biocomposite membranes were placed under the probe and tightened for measurement. -1Eight scans were performed at a resolution of 4 cm. -1 , the test results are as follows Figure 2 shown.

[0113] from Figure 2 It can be seen that compared with the degradable biocomposite membrane obtained in Comparative Example 1, the FTIR spectrum of the degradable biocomposite membrane obtained after adding whey protein isolate fibers is at 1640 cm -1 The peak at 1548 cm becomes sharper, which is the characteristic peak of amide I band; -1 A new peak appears at 3000-3700cm, and the peak becomes sharper as the protein fiber concentration increases, which is the characteristic peak of the amide II band. Both of these are related to the unconverted proteins and peptides contained in the added protein fiber solution. -1 The peak at is caused by the free stretching vibration of the hydroxyl groups between and within the molecules. It can be found that as the concentration of protein fibers increases, the hydroxyl groups shift to the left, indicating that there are intermolecular hydrogen bonds and other interactions between protein fibers and starch, which leads to a decrease in hydroxyl groups. The interaction between the two leads to good compatibility among the components of the composite film and enhanced mechanical strength.

[0114] 4.2 X-ray diffraction (XRD)

[0115] The crystallinity analysis results of the degradable biocomposite films obtained in Examples 1-3 and Comparative Example 1 are as follows: Figure 3 shown.

[0116] Depend on Figure 3 It can be seen that after adding whey protein isolate fiber, no new peaks were generated in the biodegradable biocomposite film, which indicates that the crystal type of starch has not changed. Compared with the XRD test results of the biodegradable biocomposite film without adding protein fiber, after adding protein fiber, as the concentration of protein fiber increases, its relative crystallinity increases, which is because the interaction between protein fiber and starch increases the relative crystallinity of the composite film.

[0117] In summary, the SEM images, FTIR data and XRD data indicate that there is an interaction between protein fiber and starch.

[0118] Application Examples

[0119] The degradable biocomposite films of Examples 1-3 and Comparative Example 1 were used to measure the color of fresh-cut apples to test the antioxidant properties. The specific scheme is as follows:

[0120] (1) Browning inhibition ability

[0121] Fresh apples were washed in distilled water, peeled and cut into small pieces (3×1×1 cm). The freshly cut apples were placed in the degradable biofilms prepared in Examples 1-3 and Comparative Example 1 and sealed to obtain Part A test samples and Part B test samples. The Part A test samples and Part B test samples were exactly the same. There were 3 test samples under the same conditions in the Part A test samples and Part B test samples. For example, the Part A test samples consisted of 3 apple samples respectively wrapped and sealed by the degradable biofilm prepared in Example 1, 3 apple samples respectively wrapped and sealed by the degradable biofilm prepared in Example 2, 3 apple samples respectively wrapped and sealed by the degradable biofilm prepared in Example 3, and 3 apple samples respectively wrapped and sealed by the degradable biofilm prepared in Comparative Example 1. Then, all the test samples of part A were transferred to a refrigerator at 4°C and 75% RH for storage for 5 days, and the browning of the test samples during these 5 days was observed. The test samples of the other part were transferred to an oven at 25°C and 30% RH for storage for 5 days, and the browning of the test samples during these 5 days was observed. It was found that the apple sample wrapped and sealed by the degradable biofilm prepared in Comparative Example 1 had the fastest browning speed and the most obvious color change. This is because the higher the protein fiber content, the more cysteine ​​residues with redox activity, which makes the degradable biocomposite film have high antioxidant properties. Of course, it is inevitable that the color of fresh-cut apples will eventually become consistent over time.

[0122] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any modification, equivalent substitution, improvement, etc. made by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered by the protection scope of the present invention.

Claims

1. A degradable biocomposite membrane based on protein fiber reinforcement, characterized in that: The protein fiber-reinforced degradable biocomposite membrane is prepared from a biodegradable polymer material solution, a protein fiber solution, glycerol and water. The protein fiber solution is obtained by sequentially treating protein with acid, heat and alkali. The pH value of the protein fiber solution is 2.0-7.

0. The mass fraction of protein fiber in the protein fiber solution is greater than 2.0%. The protein fiber-reinforced degradable biocomposite membrane is obtained by the following protein fiber-reinforced degradable biocomposite membrane preparation method, the protein fiber-reinforced degradable biocomposite membrane preparation method comprising the following steps: Step S1, mixing the biodegradable polymer material solution, glycerol and water, and stirring evenly at 45° C.-90° C. to obtain a standby solution; Step S2, preparing a protein fiber solution; comprising the following steps: subjecting the protein solution to an acid treatment to obtain a treatment solution with a pH of 1.0-3.0; then subjecting the protein solution to a heat treatment, i.e., heating in a water bath at 75-90° C. for 8-10 hours, stirring continuously during the heating process, and then immersing the treatment solution in an ice-water mixture and allowing it to stand to stop the reaction; then subjecting the treatment solution to an alkali treatment to adjust the pH value of the treatment solution to 2.0-7.0, to obtain a protein fiber solution; Step S3, cooling the standby solution to 40° C., then adding the protein fiber solution to the standby solution, stirring evenly, to obtain a film-forming solution; Step S4, drying the film-forming solution prepared in step S3 in an oven, and placing it in a dryer at room temperature and constant relative humidity for two days; Wherein, in step S3, the mass of the protein fibers in the membrane-forming solution accounts for ≤2% of the total mass of the membrane-forming solution.

2. The degradable biocomposite membrane based on protein fiber reinforcement according to claim 1, characterized in that: The protein fiber is whey protein isolate fiber or soy protein fiber.

3. The protein fiber-reinforced degradable biocomposite membrane according to claim 1, characterized in that: The biodegradable polymer material is one or more of polysaccharides and proteins.

4. The protein fiber-reinforced degradable biocomposite membrane according to claim 3, characterized in that: The polysaccharides include common starch, modified starch, chitosan, konjac glucomannan and pectin.

5. A method for preparing a degradable biocomposite membrane based on protein fiber reinforcement as claimed in claim 1, characterized in that: The following steps are involved: Step S1, mixing the biodegradable polymer material solution, glycerol and water, and stirring evenly at 45° C.-90° C. to obtain a standby solution; Step S2, preparing a protein fiber solution; comprising the following steps: subjecting the protein solution to an acid treatment to obtain a treatment solution with a pH of 1.0-3.0; then subjecting the protein solution to a heat treatment, i.e., heating in a water bath at 75-90° C. for 8-10 hours, stirring continuously during the heating process, and then immersing the treatment solution in an ice-water mixture and allowing it to stand to stop the reaction; then subjecting the treatment solution to an alkali treatment to adjust the pH value of the treatment solution to 2.0-7.0, to obtain a protein fiber solution; Step S3, cooling the standby solution to 40° C., and then adding the protein fiber solution to the standby solution, stirring evenly, to obtain a film-forming solution; in step S3, the mass of the protein fiber in the film-forming solution accounts for ≤2% of the total mass of the film-forming solution; Step S4: Dry the film-forming solution prepared in step S3 in an oven, and place it in a dryer at room temperature and constant relative humidity for two days.

6. The method for preparing a degradable biocomposite membrane based on protein fiber reinforcement according to claim 5, characterized in that: In step S1, when the degradable polymer material solution is a polysaccharide solution or a protein solution, the mass fraction of the degradable polymer material is 3%-10%; when the degradable polymer material solution contains polysaccharides and proteins, the mass fraction of the polysaccharide is 1%-9%, and the mass fraction of the protein is 9%-1%.

7. Use of the protein fiber reinforced degradable biocomposite film as claimed in any one of claims 1 to 4 in food preservation.

Citation Information

Patent Citations

  • Preparation method of degradable nanofiber antibacterial preservative film

    CN111286870A